1998
DOI: 10.1108/08876049810226946
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for marketing travel services to new‐age elderly

Abstract: Based on Schiffman and Sherman’s conceptual model of the new‐age elderly this article constructs a measure that identifies this segment of elderly in terms of their value orientation. The findings show that older consumers’ value orientations are an effective segmentation approach; one that is superior for partitioning the market for services like leisure travel than the traditional age‐based segmentation approach. Marketing strategy implications of the findings are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 5 publications
1
72
0
5
Order By: Relevance
“…This is because in the psychological study, many of the elderly showed that the older group tended to see themselves as younger than their real age and explains the subjective age in the definition of Cognitive age. For example, in the study by Mathur et al (1998), it was found that the cognitive ages of all groups were less than their chronological ages. Besides, it was also found that there are differences between chronological age and cognitive age when comparing the New-Age Elderly to the Traditional elderly.…”
Section: Aging Tourist Segmentation Concept Using Navo Scalementioning
confidence: 97%
See 2 more Smart Citations
“…This is because in the psychological study, many of the elderly showed that the older group tended to see themselves as younger than their real age and explains the subjective age in the definition of Cognitive age. For example, in the study by Mathur et al (1998), it was found that the cognitive ages of all groups were less than their chronological ages. Besides, it was also found that there are differences between chronological age and cognitive age when comparing the New-Age Elderly to the Traditional elderly.…”
Section: Aging Tourist Segmentation Concept Using Navo Scalementioning
confidence: 97%
“…They love to travel like those in the younger age group and join in adventure tourism activities such as rafting, etc. Mathur et al (1998) has studied the New-Age Elderly by using 257 samples of family members with a Bachelor degree or higher in Marketing, aged over 55 years old. It was found from the result of study that the average age of the New-Age Elderly was 63.3 years old by cognitive age which was less than their chronological age by 12 years.…”
Section: Aging Tourist Segmentation Concept Using Navo Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Respecto a la definición del grupo que será objeto de la presente investigación, se han considerado las personas a partir de los 55 años, decisión adoptada a partir de la revisión de la literatura, ya que el número de autores que han optado por este umbral de edad obteniendo resultados satisfactorios en sus investigaciones es numeroso (Barak y Schiffman, 1981;Moschis, 1992Moschis, , 1994Moschis, , 1996Moschis, , 2000Moschis, , 2003Marin Vidal, 1993;Cai, 1997;Dunne y Turley, 1997;Mathur, Sherman y Schiffman, 1998;Faranda y Schmidt, 1999;Shoemaker, 2000;Hsu y Lee, 2002;Reece, 2004;Wang, Norman y McGuire, 2005).…”
Section: Propuesta De Medición De La Edad Cognitivaunclassified
“…Although studies (for example Fodness & Murray, 1997, 1999Gitelson & Crompton, 1983;Mathur, Sherman & Schiffman, 1998;Pearce & Schott, 2005;Perdue, 1993;Snepenger, Meged, Snelling & Worrall, 1990;Van Raaij & Francken, 1984) had been conducted on travel information search in general, however, very few studies have been carried out in Australia (particularly in the South-East Queensland region), specifically to investigate into the information sources used for selecting travel agencies. Based on the literature, a preliminary framework (Figure 1) was developed and derived from these previous travel information search studies which had investigated into different types of information sources.…”
Section: Literature Reviewmentioning
confidence: 99%